2021
DOI: 10.1044/2020_jslhr-19-00423
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Language Disorder and Uninhibited Primitive Reflexes in Young Children

Abstract: Purpose Developmental language disorder (DLD) is a developmental disorder where children fail to acquire language in the absence of a clear cause. Many studies have reported general motor deficits in children with DLD, but no studies have uncovered a cure. The purpose of our study is to better understand the underlying motor deficits in DLD, starting from uninhibited primary reflexes—which are the most basic stage of motor development. Knowledge of this motor–language relationship should lead to ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…With the maturation of the central nervous system, these primitive reflexes become more challenging to evoke after the first year postpartum when the infant becomes capable of voluntary motor activity. RPRs are not infrequently present in children with ASD, ADHD, or cerebral palsy, and may be early indicators of brain-based deficits (3,4,22,148,(292)(293)(294)(295).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the maturation of the central nervous system, these primitive reflexes become more challenging to evoke after the first year postpartum when the infant becomes capable of voluntary motor activity. RPRs are not infrequently present in children with ASD, ADHD, or cerebral palsy, and may be early indicators of brain-based deficits (3,4,22,148,(292)(293)(294)(295).…”
Section: Discussionmentioning
confidence: 99%
“…It has been argued that independent of a child's age, RPRs are significantly related to an infant's ability to interact with objects (i.e., agency) ( 4 , 21 , 144 , 156 , 210 ) as well as with others (i.e., copying gestures) ( 22 ), meaning that high scores in the assessment of primitive reflexes, is associated with an increased likelihood of RPRs, which, in turn, are also associated with low scores in motor responsivity, independent of the age of the infant.…”
Section: Retained Primitive Reflexes Motor Function and Neurobehavior...mentioning
confidence: 99%
See 1 more Smart Citation
“…The most severe consequences of primary reflexes persistence are typically found in children with cerebral palsy, while milder persistence has been observed in children with reading difficulties and motor problems (McPhillips, Hepper & Mulhern, 2000). It has also been shown that the non-integration of primitive reflexes can cause developmental delays, and is associated with a variety of disorders, such as ADHD (Konicarova, Bob & Raboch, 2013), autism, learning difficulties (Bilbilaj, Gjipali & Shkurti, 2017;Hickey & Feldhacker, 2021;Matuszkiewicz & Ga lkowski, 2021), dyspraxia (Pecuch et al, 2020), dyslexia, behavioral disorders (Rashikj-Canevska & Mihajlovska, 2019) or sensory processing disorders (Bilbilaj et al, 2017, Rashikj-Canevska & Mihajlovska, 2019.…”
Section: Introductionmentioning
confidence: 99%
“…One factor that is not often considered when thinking about language and reading disability is the common co-occurrence of motor deficits. However, decades of research demonstrate that motor, language, and reading deficits often co-occur (Bishop, 2002;Bishop & Edmundson, 1987;Brookman et al, 2013;Hill, 2001;Matuszkiewicz & Gałkowski, 2021;Owen & McKinlay, 1997;Powell & Bishop, 1992). A cognitive theory that can reconcile this seemingly unlikely relationship is the simulation theory of reading comprehension based on embodied cognition (Barsalou, 1999;Gallese, 2007Gallese, , 2008Gallese & Lakoff, 2005;Glenberg & Robertson, 2000;Zwaan & Taylor, 2006).…”
mentioning
confidence: 99%